2021
DOI: 10.3329/brj.v25i1.55182
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Rice Cultivation under Current and Future Environment and Market

Abstract: Risk is an inevitable feature of agriculture globally, and it might increase over time in the future. The study assesses the risk of rice cultivation in the three seasons under current and future conditions. The software programme @Risk version 7.6 was used to simulate the risk-return trade of rice cultivation in the three seasons in Bangladesh. The likelihood of having negative net income for the Aus (90%) and Boro (80%) rice was very high under the current market and environmental conditions. Besides, the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…Dinajpur, one of the northern districts of Bangladesh, is known for its agricultural importance. According to Kabir et al, (2018), there was an 80-183% surplus in rice production during 2014-2015 in Dinajpur. However, this region is also known as a drought-prone area in the country.…”
Section: Introductionmentioning
confidence: 99%
“…Dinajpur, one of the northern districts of Bangladesh, is known for its agricultural importance. According to Kabir et al, (2018), there was an 80-183% surplus in rice production during 2014-2015 in Dinajpur. However, this region is also known as a drought-prone area in the country.…”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, the weather also has an impact on the quality of crops during movement from field to warehousing and then to market. 5 Adverse weather can affect the quality of products during transportation, as well as the viability and vigor of seeds and planting material during warehousing. 6 Crops and cropping systems must be matched to the meteorological requirements for maximum yield at a specific area, and pest-and diseaseprevalent seasons must be avoided.…”
Section: Introductionmentioning
confidence: 99%
“…The weather significantly influences crop growth, maturity, yields, pest and disease prevalence, and water and fertilizer needs 4 . Furthermore, the weather also has an impact on the quality of crops during movement from field to warehousing and then to market 5 . Adverse weather can affect the quality of products during transportation, as well as the viability and vigor of seeds and planting material during warehousing 6 .…”
Section: Introductionmentioning
confidence: 99%
“…The average cropping intensity of Haor areas is 176% (Table 3) as reported by the DAE [3]. Haor regions play a crucial role by (i) contributing around 18% of the overall Boro rice production [5] and (ii) generating job opportunities for non-farm wage employees by harvesting Boro rice about one month before other locations [6]. Data presented in the Table 4 shows that Haor districts and regions account for around 19% and 9% of the nation's total Boro rice acreage, respectively [7].…”
Section: Introductionmentioning
confidence: 99%
“…Data presented in the Table 4 shows that Haor districts and regions account for around 19% and 9% of the nation's total Boro rice acreage, respectively [7]. Kabir et al [6] also reported that about 36% of the land is under Boro rice cultivation in Sunamganj compared to 23% in Kishoreganj and 11% in Habiganj (Figure 4). Around 22 to 73% of the total land area is under cultivation (Figure 5).…”
Section: Introductionmentioning
confidence: 99%